2002
DOI: 10.1177/174182670200900404
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Risk Factors and Prophylactic Drug Usage in Turkish Patients with Angiographically Established Coronary Artery Disease

Abstract: Background Coronary artery disease (CAD) is the leading cause of adult deaths in our country. In clinical practice, an adequate level of secondary prevention towards CAD primarily requires full recognition of the distribution of risk factors. The aim of our study was to determine the prevalence of coronary risk factors and the use of prophylactic drugs among patients who have an angiographically proven CAD in our centre, and to compare it with those of the EUROASPIRE I and II studies.Design Cross-sectional, ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(24 reference statements)
1
3
0
Order By: Relevance
“…An interesting finding in the present study was that CAD risks varied along with the type of valve disease as previously reported [Emren 2014;Sonmez 2002]. Thalji and colleagues found that patients with aortic valve diseases were more likely to have CAD than those with mitral valve diseases [Thalji 2013], which also was observed in our investigation.…”
Section: Discussionsupporting
confidence: 86%
“…An interesting finding in the present study was that CAD risks varied along with the type of valve disease as previously reported [Emren 2014;Sonmez 2002]. Thalji and colleagues found that patients with aortic valve diseases were more likely to have CAD than those with mitral valve diseases [Thalji 2013], which also was observed in our investigation.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have revealed increased plasma levels of TNF-α and of CRP in smokers as compared to non-smokers [10,11], suggesting that part of the coronary risk associated with smoking may relate to increased inflammatory activity. However, the prevalence of cardiovascular disease varies substantially among smoking individuals [12]. This could indicate that genetic factors are important determinants of the biological pathways linking smoking with cardiovascular disease risk [13].…”
Section: Introductionmentioning
confidence: 99%
“…The demographic information was obtained from the census data that covered whole country, the risk factor trends were obtained from national epidemiological studies. Treatment uptake data was obtained from multicentre national studies (EUROASPIRE III [ 26 ], PREMISE [ 27 ]) and from a hospital based surveys conducted in recent years [ 43 , 61 , 62 ]. Certain assumptions were therefore taken to fill in the gaps for missing information including specific patient groups’ data.…”
Section: Discussionmentioning
confidence: 99%